„Witch Ple-Ple” as a teacher. You’re going to scare you in art education? - Wnuk, Kamil (Nauczyciel wczesnej edukacji wobec zmian społeczno-kulturowych, 2016)
By using an expression „ple-ple” the author points our attention to the problem of creating a sense and also to the reflection on the subject of Art Education which is becoming more and more socially established and understood activity. Understanding the phenomenon of taking part in the culture by the new media, new models of cooperation, cultural activity is also changing nowadays. The exchange of ideas, opinions and information among young people is taking place in a real time. On one hand, this fact can arouse justified fascination about new media among the reseachers. On the other hand, it can start theoretical and methodogogical ferment when it comes to the research. The research show us lack of teachers preparation to artistic tasks they are given and the only exception can be the teaching functions. The practical knowledge category is connected with the knowledge created by the teachers and, to some degree, it is unique - the knowledge that is represented by the rules and the proceeding in the specific school situations.